2019
DOI: 10.2478/sh-2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

AI Case Studies: Potential for Human Health, Space Exploration and Colonisation and a Proposed Superimposition of the Kubler-Ross Change Curve on the Hype Cycle

Abstract: The development and deployment of artificial intelligence (AI) is and will profoundly reshape human society, the culture and the composition of civilisations which make up human kind. All technological triggers tend to drive a hype curve which over time is realised by an output which is often unexpected, taking both pessimistic and optimistic perspectives and actions of drivers, contributors and enablers on a journey where the ultimate destination may be unclear. In this paper we hypothesise that this journey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Our findings revealed stepney was not meeting the standards. It is also evidenced from our study that fire extinguisher was not meeting the standards while studies 29 have suggested that it is important to have fire extinguisher in the ambulance to prevent worsening of the situation in case of a fire emergency.…”
Section: Discussionmentioning
confidence: 69%
“…Our findings revealed stepney was not meeting the standards. It is also evidenced from our study that fire extinguisher was not meeting the standards while studies 29 have suggested that it is important to have fire extinguisher in the ambulance to prevent worsening of the situation in case of a fire emergency.…”
Section: Discussionmentioning
confidence: 69%
“…which may place extra demand on the supply chain of consumable products. Some of the many current and emerging technologies to assist space travelers and colonists shown in Table 4 include the consideration of ergonomic design and how AI may play a role [66,67] based on the momentum for AI in terrestrial healthcare management (e.g., Bohr & Memarzadeh 2020 [68]). Delivery of drugs via impregnated bandages (e.g., Maver et al [69]) or nano-fluidics where a tunable supply of the beta-agonist formoterol from a nano-reservoir has been demonstrated to reduce muscle atrophy in mice [70] and may form the start of a promising modality which was recently been reviewed [71].…”
Section: Emergency Evacuation Protocol and Processes Clinical Waste M...mentioning
confidence: 99%